2006
DOI: 10.1111/j.1365-2761.2006.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infections with Lepeophtheirus salmonis (Krøyer) on threespine sticklebacks, Gasterosteus aculeatus L., and juvenile Pacific salmon, Oncorhynchus spp.

Abstract: Experimental infections with Lepeophtheirus salmonis (Krøyer) were established on threespine sticklebacks, Gasterosteus aculeatus L., juvenile pink, Oncorhynchus gorbuscha (Walbaum), and chum, Oncorhynchus keta (Walbaum), salmon. The prevalence and abundance of infections were initially higher on sticklebacks than on either salmon species. The initial prevalence and intensity of infections on chum salmon were higher than those on pink salmon, and declined on both species during louse development. The rate of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
2
60
1
Order By: Relevance
“…For example, a well-developed tissue response occurs at the site of louse attachment on coho salmon Oncorhynchus kisutch 1 d post infection, whereas the reaction is markedly reduced or absent in Chinook salmon O. tshawytscha and Atlantic salmon (Johnson & Albright 1992). Similarly, the intensity of L. salmonis was significantly lower on coho salmon when compared to Atlantic salmon and rainbow trout O. mykiss (Fast et al 2002), and pink salmon O. gorbuscha rejected L. salmonis more rapidly than chum salmon O. keta during laboratory challenges (Jones et al 2006(Jones et al , 2007. The rejection of lice observed in the latter study is associated with an earlier and quantitatively higher expression of proinflammatory genes in pink salmon (Jones et al 2007).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, a well-developed tissue response occurs at the site of louse attachment on coho salmon Oncorhynchus kisutch 1 d post infection, whereas the reaction is markedly reduced or absent in Chinook salmon O. tshawytscha and Atlantic salmon (Johnson & Albright 1992). Similarly, the intensity of L. salmonis was significantly lower on coho salmon when compared to Atlantic salmon and rainbow trout O. mykiss (Fast et al 2002), and pink salmon O. gorbuscha rejected L. salmonis more rapidly than chum salmon O. keta during laboratory challenges (Jones et al 2006(Jones et al , 2007. The rejection of lice observed in the latter study is associated with an earlier and quantitatively higher expression of proinflammatory genes in pink salmon (Jones et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The water flow was stopped, tank volume was reduced to approximately 90 l, aeration was maintained, and the water was supplemented with 0.2 mg l −1 metomidate hydrochloride (Syndel Laboratories) as a sedative (Jones et al 2006). Copepodids were added to each tank as described below.…”
Section: Exposure To Lepeophtheirus Salmonismentioning
confidence: 99%
“…In British Columbia, field surveys found that not only were juvenile pink and chum salmon infested, but 84 per cent of sticklebacks Gasterosteus aculeatus L. also were, of which 97 per cent were copepodite and chalimus stages (Jones et al 2006a). However, laboratory studies found a loss of lice on all three hosts over time, and no mature L. salmonis occurred on sticklebacks (Jones et al 2006b). Neither the source nor fate of these lice was known, but some may re-infest other fishes.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…This sea louse occurs naturally on salmonids in the northern hemisphere, and it is not considered unusual for wild salmonids to carry a few individuals (Tingley et al 1997, Urquhart et al 2008. L. salmonis is largely specific to salmonids, and although infections have occasionally been reported in other groups of fish (Jones et al 2006a, these should be considered as unusual (Kabata 1979) and may not enable the parasite to complete its lifecycle (Jones et al 2006b). Among Norway, Scotland and Canada, L. salmonis costs the aquaculture industry approximately 70 million GBP per annum (Heuch et al 2005).…”
Section: Introductionmentioning
confidence: 99%